Advantages of Artificial Intelligence and Its Relevance in Improving Educational Quality - Ramadhan, Muhammad Qadri; Azani, Mohammad Zakki; Abdala, Gheida (Universitas Muhammadiyah Surakarta, 2024)
Artificial Intelligence (AI) is a nascent and transformative technology that has the potential to permeate and modify many aspects of our existence. It has developed as a recent phenomenon in the realm of education. This research specifically examines the difficulties and advantages associated with Islamic Education in the contemporary digital era. The objective of this study is to offer a comprehensive analysis of the present condition of Islamic education in the Islamic World. The study technique involves performing a comprehensive library search and collecting data from written sources about the stated subjects. The descriptive-analytical method is used in the discussion method to clarify and elaborate on the key concepts pertaining to the subjects covered. The results show that AI education (AIED) is an emerging field of scientific research for more than 30 years. It is aimed at preparing students with the ability to think critically and solve problems, being able to develop interpersonal communication well, creatively, and, of course, collaboratively, and change the mindset of teachers and other education stakeholders to be more adaptive to technological developments in learning. It is essential to equip students with virtuous values, particularly Islamic values, in order for them to mature into faithful Muslim individuals who possess everlasting faith and reverence towards Allah SWT and demonstrate an outstanding character in their personal, social, national, and state endeavors.